Analysis of Korean wine market and exportation of galician wines to South Korea - Donapetry, Marta Santamaría (2022)
Wine trends have been changing along the years. Spain is a large producer and exporter of wines and within this country, Galicia is among the top 3 regions for wine exportation. On the other side, South Korea has boosted it wine consumption. Regarding several statistical data, about 80% of the wine consumed in this country, comes from foreign countries. Change in consumer´s taste (evolution), a higher concern regarding their health (wine health benefits), a gradual development of the Korean wine market (higher wine purchasing), wine festivals, and of course, COVID, are factors that help increase wine consumption in this country and that make this destination perfect for exporting this outstanding beverage from Spain to South Korea. Data collection will be performed in Seoul, South Korea, with a mix between quantitative and qualitative research. Both interview and surveys will develop in two languages, Korean and English. Besides, observation will also be applied for the market analysis investigation in situ. The wine sector is evolving in an increasingly competitive international scene characterised by the emergence of new wine-producing countries using innovative production and marketing strategies to capture a growing share of trade. COVID 19 and isolation time, has caused an exponential increase of alcohol consumption worldwide. Wine, especially, has been favoured by this pandemic.